Chilly Climate 2.0: Women’s Experiences of Harassment and Discrimination in Canadian Higher Education - Hughes, Janette; Scott, Hannah; Morrison, Laura Jane; Kotsopoulos, Donna; Ruttenberg-Rozen, Robyn (Canadian Journal of Education / Revue canadienne de l'éducation, 2023)
This research examines the extent to which issues identified in Breaking Anonymity (The Chilly Collective, 1995) are still salient despite new EDI mandates/programs which support increased research excellence through EDI principles. We present survey results for Canadian academics who identify as women (n = 244) regarding their experiences with gender-based harassment and discrimination. Our analysis identified three categories of patriarchal gendered control: (1) overt practices, (2) covert practices, and (3) a systematic effort to silence the reporting of these experiences. We highlight the voices of women academics as they provide personal insights into the continuing barriers through their experiences. Through their stories, the implications of existing overt and covert harassment and discrimination practices are discussed. Our study provides an overview of women academics’ experiences with oppression by their male colleagues and contributes to research exploring equity and inclusion in higher education and the continued need to work toward gender equity.